Association of Riverside Living with SIRS Incidence in Stroke Patient in South Kalimantan - Fakhrurrazy Fakhrurrazy; Pagan Pambudi; Ananda Dwi Latifah; Asti Afrida Yanti; Siti Habibah Zein; Husnul Khatimah; Anggun Wulandari (Gema Lingkungan Kesehatan, 2026)
South Kalimantan is a province that has 97 rivers, and many people who live on the riverside make the rivers a source of life. Currently, there is more and more river water pollution, which has an impact on the health status of people living on the riverside, especially inflammation. This study used an analytic-observational design. The study subjects were stroke patients who were treated at the stroke unit and nerve ward at Ulin Hospital, Banjarmasin, for the period October 2022-May 2023. There were 128 subjects who were divided into two groups based on whether they lived on the riverside (64 people) or not (64 people). Variable analysis used descriptive analysis, the chi-square test, and multivariate analysis using the logistic regression test. Based on the descriptive analysis, it was found that there were no variables that showed meaningful results. Bivariate analysis resulted in variables that had a significant relationship. In the multivariate analysis, it was found that living on the riverside and mortality rate were independent predictors, which together with the dependent predictor factor, i.e., the type of stroke, affected the incidence of SIRS in stroke patients. Living on the riverside and mortality can be used as predictors of SIRS in stroke patients. SIRS assessment in an appropriate manner in stroke patients who live on river banks should be a routine examination. Prevention and monitoring of risk factors can prevent stroke patients from experiencing SIRS conditions to avoid complications that can occur.